Current Account Imbalances: Signs of Adjustment? - Fuchs,Philipp (2015)
Global external imbalances are commonly labelled as one of the main reasons for the Global Financial Crisis. This paper investigates these imbalances and determines current account equilibria for 21 OECD countries. Subsequently, we measure the speed of adjustment to the calculated equilibrium values and test for asymmetric adjustment effects. We extend the approach of Gossé and Serranito (2014) in updating and extending their dataset and testing additional variables like the net foreign assets, population growth and trade openness. We find negative threshold values of around 3.8% below equilibrium. Countries below this threshold adjust significantly faster than countries above.
Keywords: dynamic ordinary least squares; panel cointegration; Current account imbalances; asymmetric panel VECM; threshold effects